Comparative analysis of microbiota in the ceca of broiler chickens with necrotic enteritis fed a commercial corn diet or with corn high in flavonoids (PennHFD1) - Miska, Katarzyna B.; Proszkowiec-Weglarz, Monika; Buiatte, Vinicius; Mahmoud, Mahmoud; Lesko, Tyler; Jenkins, Mark C.; Chopra, Surinder; Lorenzoni, Alberto Gino (Frontiers in Microbiomes, 2023)
Necrotic enteritis (NE) is a disease of the gastrointestinal tract that is common in broiler chickens and causes substantial economic losses to the poultry industry worldwide. The removal of many antimicrobials in poultry diets has driven the search for alternatives. The purpose of this study was to determine the microbiota changes in the cecal luminal (CE-L) and mucosal (CE-M) populations of broiler chickens undergoing clinical NE (co-infected with Eimeria maxima and Clostridium perfringens) while fed a diet containing a flavonoid rich corn (PennHFD1) or control diet using commercial corns. It was previously shown that chickens fed a diet high in flavonoids had improved performance parameters, lower mortality rate, and lower incidence of intestinal lesions. Flavonoids have been shown to have anti-bacterial, immuno-modulatory, and anti-inflammatory activity. The current study included four experimental groups: infected chickens fed commercial corn diet (CTRL-A) or PennHFD1 (CTRL-B) and infected chickens fed commercial corn diet (IF-A) or PennHFD1 (IF-B). We found that most of the microbiota changes were due to infection rather than diet. The alpha diversity in the IF chickens was lower in both CE-L and CE-M. The beta diversity of microbial communities was different between IF and CTRL chickens, as well as between CTRL-A and CTRL-B. The beta diversity of CTRL birds was more homogenous compared to IF samples. Taxonomic analysis showed a decrease in short chain fatty acid producing bacteria in IF birds. An This is a provisional file, not the final typeset article increase in lactic acid producing bacteria, Escherichia coli, and Enterococcus cecorum was also observed in IF birds. It is possible that the effect of the high flavonoid corn on the microbiota was overcome by the effect of NE, or that the positive effects of increased flavonoids in NE-challenged birds are a result of mechanisms which do not involve the microbiota. The effects of high flavonoid corn on NE infections may be further investigated as a possible alternative to antimicrobials.